Emotional and behavioural problems among children: issues and trends in Malaysia - Idayu Badilla Idris (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Emotional and behavioural problems among children have been increasing in many western as well as the eastern countries. Although the problem has been given attention and priority in terms of early detection, many children with early symptoms of emotional and behavioural problems has still not been detected at the early stages. This phenomenon is worrying as mental health problems were shown to be stable in the long run and if left undetected it may manifest into various problems in adulthood. This paper explores the issues on emotional and behavioural problems in terms of its definition, prevalence, aetiology, long term consequences and treatment. It also explores on mental health problems in a non-western country, i.e. Malaysia including its prevalence and intervention strategies which has been carried out in overcoming this worrying issue. Finally this review paper stresses the importance of providing a well-designed epidemiological study in Malaysia in assessing the current prevalence of emotional and behavioural problems in young children and adolescent.